1995
DOI: 10.1038/hdy.1995.8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genetic factors controlling pollen–style interaction in maize

Abstract: In order to detect loci specifically related to pollen-style interaction in maize, linkage analysis to RFLP markers was performed on a population of recombinant inbred lines, the pollen of which was used to pollinate female plants of two different genotypes: the F1 from which the recombinant inbred population was derived ('self female') and a genetically unrelated hybrid genotype ('cross female'). Besides pollen grain germinability and pollen tube growth rate on the two females, pollen general competitive abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…(1996 ) showed that self pollen penetrate the stigma surface in significantly lower proportions than outcross pollen (23–37% and 80–84%, respectively). This germination difference is much larger than the fitness differences we estimated between self and outcross pollen, suggesting either that stigma penetration is more even in our material, or that the difference disappears later in the life of pollen tubes ( Sari‐Gorla et al ., 1995a , b).…”
Section: Discussioncontrasting
confidence: 59%
“…(1996 ) showed that self pollen penetrate the stigma surface in significantly lower proportions than outcross pollen (23–37% and 80–84%, respectively). This germination difference is much larger than the fitness differences we estimated between self and outcross pollen, suggesting either that stigma penetration is more even in our material, or that the difference disappears later in the life of pollen tubes ( Sari‐Gorla et al ., 1995a , b).…”
Section: Discussioncontrasting
confidence: 59%
“…The small differences could not be explained by the number of pollen tubes in the style, or by early pollen tube growth rate. A negative correlation between early pollen tube growth and late pollen tube growth has been shown for maize (Sari-Gorla et al 1995). If a similar negative correlation holds true for E. vulgare, competition between pollen tubes at a later stage could explain the ifferences between the two experiments in siring success of the cross-pollen donors.…”
Section: Discussionmentioning
confidence: 65%
“…Pollen germination, pollen-tube growth, and fertilization ability have been shown to differ significantly among recipients from different subspecies (Carney et al, 1994), different inter-mate distances (Waser et al 1987, Cruzan 1990, Waser and Price 1991, and different recipient genotypes (Pfahler 1967, Pittman and Levin 1986, Fenster and Sork 1988, Aizen et al 1990, Marshall and Folsom 1991, Snow and Spira 1992, Cruzan 1993. These effects of recipients on pollen performance or fertilization ability have been attributed to differences in both the growth environment of recipient plants (Fenster andSork 1988, Marshall andFolsom 1991) and genetic make-up of recipients (Pfahler 1967, Pittman and Levin 1986, Cruzan 1990, Sari-Gorla et al 1995). In the current study, front distances differed between sibships of recipient plants in C. unguiculata, suggesting that recipient influences on pollen performance were inherited from their maternal parent.…”
Section: Discussionmentioning
confidence: 99%